Efektivitas Penambahan Bahan Pengenyal yang Berbeda terhadap Kandungan Lemak dan Susut Masak Bakso Daging Ayam Broiler - Nasrul, Nasrul; Novieta, Intan Dwi; Irmayani, Irmayani (Fakultas MIPA UNM, 2019)
Abstract. The purpose of this study was to determine the effect of addition of chewing agents which differed on broiler chicken meatballs. The results of study show that with the addition of different ingredients that are egg white, carrageenan and gelatin have a very real effect. The average value of the highness fat content at the lowest is T3 at (0,71) T1 at (0,64) T2 at (0,61) and T0 at (0,51). The highest average cooking shrinkage value is T0 of (31,15) T1 of (20,82) T2 of (16,77) and T3 of (2,35). From the results of this study, it is known recommended is T0 treatment for fat content and T3 treatment for cooking losses.Keywords: Fat content, Cooking shrinkage, Egg white, Carrageenan, and Gelatin